Managing Public Trust (Springer International Publishing, 2018)
This book brings together the theory and practice of managing public trust. It examines the current state of public trust, including a comprehensive global overview of both the research and practical applications of managing public trust by presenting research from seven countries (Brazil, Finland, Poland, Hungary, Portugal, Taiwan, Turkey) from three continents. The book is divided into five parts, covering the meaning of trust, types, dimension and the role of trust in management; the organizational challenges in relation to public trust; the impact of social media on the development of public trust; the dynamics of public trust in business; and public trust in different cultural contexts. Barbara Kożuch is Professor of Economic Sciences at Jagiellonian University in Kraków, Poland, and a specialist in Organisation Theory and Public Management. Slawomir J. Magala is Professor of Cross-Cultural Management in the Department of Organizational Sciences and Human Resource Management at the Rotterdam School of Management, Erasmus University, the Netherlands. Joanna Paliszkiewicz is Professor at the Warsaw University of Life Sciences - SGGW, Poland, and at the Polish Japanese Academy of Information Technology.